Polymerase Chain Reaction (PCR) Technique in Detection of Actinomyces SPP by Using Cervico-Vaginal Fluid Samples - Dilek Kaya (Medical Network, 2011)
OBJECTIVE: To detect the most common Actinomyces species correctly in cervico-vaginal fluid samples by using Polymerase Chain Reaction (PCR) technique. STUDY DESIGN: Cervico-vaginal fluid samples were obtained from 200 patients and bacterial genomic DNA was isolated directly from samples of each patient. The PCR technique was used for two purposes. First was applied for the detection of Actinomycetales including the genus Actinomyces and second was used for the differentiation of Actinomyces spp from each other. RESULTS: Actinomycetales was detected in 16 (8%) of 200 samples by PCR. In these 16 examined samples, 8 were positive for at least one of the following three species, namely A. meyeri (2.5%), A. viscosus (1%) and A. israelii (0.5%). No A. odontolyticus was detected in any of the fluid samples. CONCLUSION: PCR was shown to be a simple, rapid and highly discriminatory method for the identification and differentiation of Actinomyces spp in examining cervico-vaginal fluid samples.